An Examination of a Play-Based Summer Reading Program for Elementary-Aged Children with Reading Difficulties - Parr, Lindsay (Université d'Ottawa / University of Ottawa, 2022)
Recent research suggests that summer reading programs may benefit elementary-aged children with learning disabilities and reading difficulties. However, there exists limited literature on how both play-based learning (PBL) and scaffolding can be used to improve reading outcomes in non-school settings. The purpose of this qualitative research was to examine PBL, scaffolding, and perceived reading outcomes in a 6-week play-based summer reading program. The conceptual framework guiding this research is that PBL, when combined with scaffolding, results in either the maintenance or the improvement of reading outcomes. Fourteen individuals (5 support workers, 4 parents, 5 children) who were enrolled in a play-based summer reading program between 2019 and 2021 participated in semi-structured interviews. The findings suggest that PBL and scaffolding can lead to perceived reading progress and increases in confidence and motivation, as well as an absence of a summer learning slide. Additional themes relating to the role of the support workers, program organization and friendship/belonging emerged. Implications for the literacy learning of elementary-aged children with disabilities and reading difficulties are discussed.
Keywords: play-based learning; summer reading programs; scaffolding; reading difficulties